New Phytol Derivatives with Increased Cosmeceutical Potential - Rosa, Gonçalo P. (2024)
Natural compounds are widely incorporated into cosmetic products for many purposes. Diterpenes often function as fragrances, enhancing the sensory experience of these formulations. However, current trends in cosmetic science aim to develop multifunctional products, where compounds traditionally used for texture or fragrance also possess biological activities that contribute to the product’s efficacy. In this context, this study focuses on synthesizing derivatives of phytol—a compound already presents in cosmetic formulations—to enhance its anti-aging properties. The derivatives were synthesized through esterification with substituted benzoic and cinnamic acids, known for their antioxidant and enzyme inhibition properties. Reaction yields ranged from 91.0% to 5.2%, depending on the substituents in acid derivatives. The structures of the synthesized compounds were confirmed through NMR and MS techniques. Both the natural and newly synthesized derivatives were evaluated for their cosmeceutical potential using antioxidant assays and inhibition assays for tyrosinase, elastase, collagenase, and hyaluronidase. This work presents the first report of the synthesis and cosmetic evaluation of several of these derivatives. Comparing with phytol (1), which presented an IC50 of 77.47 µM, four of the derivatives presented improved tyrosinase inhibitory activity, with phytyl 4-methoxybenzoate being the most active (IC50 = 27.9 µM), followed by phytyl benzoate with an IC50 of 34.73 µM. Substitutions at other positions on the aromatic ring were less effective. Molecular docking studies confirmed that the modifications potentiated a stronger interaction between the synthesized compounds and tyrosinase.